Answer:
Since all parts of 2i(-3+7i) is in the denominator, you have to use an extra set of parentheses around the whole denominator. this is what you do
(5+i)(6−5i) / (2i(−3+7i))
= (30−25i+6i−5i^2) / (−6i+14i^2)
= (35−19i) / (−14−6i)
= (35−19i)(−7+3i) / (2(−7−3i)(−7+3i))
= (−245+105i+133i−57i^2) / (2(49−9i^2))
= (−188+238i) / (2(58))
= (−188+238i) / 116
= −47/29 + 119/58 iso that is how you do it
Remember PEMDAS
first add -3p^2 and 7p^2 to get 4p^2.
next add 8p^2 and 4p^2 to get 12p^2
12p^2 is your answer
Wheres the data? we cant answer without the data.
Answer:
4608*sqrt(3)
Step-by-step explanation:
x + 2x = 3x, so 3x is the height of the triangle. This is a 90-60-30 triangle so the base would be 3x*sqrt(3). To find the area, we can multiply the base with the height and divide by two, so it would be (3x)(3x*sqrt(3))/2 or (9/2)x^2 * sqrt(3). x = 32, and plugging this into the equation gets us to (9/2)32^2 * sqrt(3), which is 4608*sqrt(3).